Methanol synthesis in a three‐phase catalytic bed under nonwetted condition. Issue 1 (28th October 2016) - Ling, Dan; Liu, Peng; Cheng, Zhen‐Min
Abstract : To overcome the heat removal problem encountered in methanol synthesis at high syngas concentrations in the gas phase, a three‐phase nonwetted catalytic system was established by introducing an inert liquid medium into a fixed‐bed reactor. To form a repellent interface between the liquid and the catalyst, the catalyst was modified into hydrophobic, while the liquid medium was chosen as a room temperature ionic liquid with hydroxyl groups. The liquid‐solid contact angle was measured to be 115°, and only 20% of the catalyst external surface was wetted by the liquid. Under three‐phase condition, the reaction rate was measured to be 60%–70% of gas‐phase reaction, while it was merely 10%–20% for the fully wetted catalyst. From the resistance analysis on the mass transfer and reaction steps, the overall reaction rate is expected to increase further if the surface could be more wet proofed. © 2016 American Institute of Chemical Engineers AIChE J, 63: 226–237, 2017